PEMBERDAYAAN UMKM MELALUI PEMANFAATAN MEDIA SOSIAL SEBAGAI SARANA PROMOSI DIGITAL DI PEKON YOGYAKARTA KECAMATAN GADINGREJO KABUPATEN PRINGSEWU - Hendra Widodo; Yudi Eka Putra (Jurnal Pengabdian Kepada Masyarakat Sakai Sambayan, 2026)
This community service program was implemented as a form of contribution to support the strengthening of the Micro, Small, and Medium Enterprises (MSME) sector in Pekon Yogyakarta, Gadingrejo Sub-district, Pringsewu Regency. The primary focus of this initiative is to enhance the promotional capabilities of MSMEs through the use of simple yet effective digital media. Three main strategies implemented in this activity include: creating promotional mini-vlogs through the Instagram platform, designing business banners as visual identities, and adding MSME locations to Google Maps services to make it easier for consumers to find business locations directly. This activity was designed to address the challenges faced by MSMEs in terms of limited access to and understanding of information technology as a marketing tool. The results of the program indicate an increase in business owners' awareness of the importance of digital presence and a growing enthusiasm for utilizing social media in a more targeted manner. With this approach, it is hoped that local SMEs will be able to expand their market reach, build a more professional business image, and gradually adapt to the developments in the digital economy.